1997
DOI: 10.1111/j.1432-1033.1997.0122a.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Carbohydrate Backbone of the Lipopolysaccharide from Acinetobacter Strain ATCC 17905

Abstract: The structure of the carbohydrate backbone of the lipopolysaccharide from Acinetobacter strain ATCC 17905 was studied. After deacylation of the lipopolysaccharide, a mixture of two compounds (ratio approximately 2 : 1) was isolated by high-performance anion-exchange chromatography, the structures of which were determined by NMR spectroscopy and electrospray-mass spectrometry as cr-Glc-(l-6)-j-Glc-(l-3)-~-Gal-(1-7)-a-Kdo[Sug, 3-deoxy-~-manno-2-octulopyranosonic acid (Kdo) in oligosaccharjde 1 (major portion) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 25 publications
0
34
0
1
Order By: Relevance
“…Previous studies have unambiguously shown that the lipid A disaccharide backbone of Acinetobacter spp. is composed of two ␀-(1-6)-linked 2-amino-2-deoxyglucose residues (GlcNI and GlcNII) phosphorylated at positions 1 and 4Ј (22,23,49). The lipid A fraction of A. baumannii contains two major species which may correspond to a hepta-acylated lipid A with two 2-amino-2-deoxyglucose residues, two phosphates, (22) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have unambiguously shown that the lipid A disaccharide backbone of Acinetobacter spp. is composed of two ␀-(1-6)-linked 2-amino-2-deoxyglucose residues (GlcNI and GlcNII) phosphorylated at positions 1 and 4Ј (22,23,49). The lipid A fraction of A. baumannii contains two major species which may correspond to a hepta-acylated lipid A with two 2-amino-2-deoxyglucose residues, two phosphates, (22) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two Kdo residues are usually present, one of which is linked directly to lipid A. A subset of Gramnegative bacteria, including B. cepacia (10-12), Y. pestis (13,14), and some strains of Acinetobacter (26,27), contain an unusual analog of Kdo, known as Ko, in which the axial hydrogen atom at position 3 of Kdo is replaced with an OH group (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
“…NMR spectra were assigned by using the program Pronto [12] and NMR, GC, GC-MS, methylation and monosaccharide analysis was performed as previously described. [13,14] Preparation of core oligosaccharides and oligosaccharides 1 ± 3: LPSs from serotypes O27 and OX2 (200 mg each) were hydrolyzed with 2 % acetic acid (100 8C, 5 h). The resulting precipitate removed by centrifugation, and the supernatant separated on a Sephadex G50 SF gel (Pharmacia) column (2.5 Â 80) using pyridine/acetic acid buffer (4 and 10 mL in 1 L water) and monitoring by Waters differential refractometer.…”
Section: Methodsmentioning
confidence: 99%